ANALYSIS OF INNOVATIVE DEVELOPMENT OF HEALTHCARE INSTITUTIONS AS A FUNCTION OF THE MANAGEMENT OF THEIR SYSTEMIC DEVELOPMENT - BILETSKA, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article investigates the problems of innovative development of enterprises in modern conditions of management and competition. The urgency of improving the innovative management of health care facilities is indicated. It is concluded that the current methodological approaches to the analysis of innovation activities of enterprises are insufficient and they need further improvement.The purpose of the article is to substantiate the new methodological and applied principles of analyzing the innovative activities of health care institutions in the context of improving control as a function of management of their further development.Leading methods of evaluation of innovation activity, innovation potential and innovative development of enterprises are generalized. The components and indicators of evaluation of innovative development of health care institutions are determined. An algorithm for comprehensive assessment of innovative development of health care facilities has been developed.The peculiarities of the management of innovative development of health care institutions have been identified, among which the risk of making a wrong management decision is increased; availability of a differentiated institutional and legal basis for regulating the innovation sphere for enterprises providing medical services; strategic focus of enterprises on the development of service and product innovations; limited state support for innovation; the presence of risks of leakage of information containing trade secrets.The applied significance of the research results lies in the qualitative and thorough analysis of innovation activity, and, consequently, the adoption of more informed management decisions for their further development.The scientific novelty of the research results is the further development of methods for analyzing the innovative development of health care facilities as one of the basic functions of their management.
Keywords: management; enterprise management; health care institutions; innovative development; methods of analysis